Efficient metrics for the detection of partial discharges under steep-fronted voltage pulses. (October 2022) - Martínez-Tarifa, Juan Manuel; Granado, Joaquín; Robles, Guillermo
Abstract: The increasing use of power electronic inverters in electrical drives is leading to the unexpected inception of partial discharges (PD) within the insulation system of electric machine stator windings. Unfortunately, the short rise and fall times of such voltages, below 100 nanoseconds in most cases, create high-magnitude conducted and radiated interferences that affect the measurements. Detecting partial discharges in these systems with inductive or electromagnetic sensors turns to be an important challenge, especially when interference and partial discharges share the same bandwidth. In this work, the authors propose a technique to detect the occurrence of PD in such systems, even when they are masked by disturbances. The proposed technique combines an analog high-pass filter stage and a digital band-pass to select a proper spectral interval. The resulting signal is converted to the base-band, where two metrics based on the peak-to-average power ratio are proposed. Experimental results obtained with the signals acquired with two antennas show that both proposed metrics exhibit a significant increase, about ten times greater, when the applied voltage exceeds the PD inception voltage. These contributions define new markers for the detection of PD events created by pulsed voltages with overlapped overshoots with promising results. Highlights: Partial discharges are masked by steep-fronted pulses with superimposed overvoltages. New metrics are proposed to unmask and detect partial discharges in insulation systems. Metrics are based on the peak-to-average power ratio of two base-band signals. Metrics exhibit a significant increase when partial discharges are present. Successful detection is shown with real signals captured with two types of antenna.